Efficacies of High-Dose Fluconazole plus Amphotericin B and High-Dose Fluconazole plus 5-Fluorocytosine versus Amphotericin B, Fluconazole, and 5-Fluorocytosine Monotherapies in Treatment of Experimental Endocarditis, Endophthalmitis, and Pyelonephritis Due to Candida albicans - Louie, Arnold (American Society for Microbiology, 1999)
We compared the efficacies of fluconazole (Flu), amphotericin B (AmB), and 5-fluorocytosine (5FC) monotherapies with the combination of Flu plus 5FC and Flu plus AmB in a rabbit model of Candida albicans endocarditis, endophthalmitis, and pyelonephritis. The dose of Flu used was that which resulted in an area under the concentration-time curve in rabbits equivalent to that seen in humans who receive Flu at 1,600 mg/day, the highest dose not associated with central nervous system toxicity in humans. Quantitative cultures of heart valve vegetations, the choroid-retina, vitreous humor, and kidney were conducted after 1, 5, 14, and 21 days of therapy. All untreated controls died within 6 days of infection; animals treated with 5FC monotherapy all died within 18 days. In contrast, 93% of animals in the other treatment groups appeared well and survived until they were sacrificed. At day 5, the relative decreases in CFU per gram in the vitreous humor were greater in groups that received Flu alone and in combination with 5FC or AmB than in groups receiving AmB or 5FC monotherapies (P < 0.005) but were similar thereafter. In the choroid-retina, 5FC was the least-active drug. However, there were no differences in choroidal fungal densities between the other treatment groups. On days 5 and 14 of therapy, fungal densities in kidneys of AmB recipients were lower than those resulting from the other therapies (P < 0.001 and P ≤ 0.038, respectively) and AmB-plus-Flu therapy was antagonistic; however, all therapies for fungal pyelonephritis were similar by treatment day 21. While fungal counts in cardiac valves of Flu recipients were similar to those of controls on day 5 of therapy and did not change from days 1 to 21, AmB therapy significantly decreased valvular CFUs versus Flu at days 5, 14, and 21 (P < 0.005 at each time point). 5FC plus Flu demonstrated enhanced killing in cardiac vegetations compared with Flu or 5FC as monotherapies (P < 0.03). Similarly, the combination of AmB and Flu was more active than Flu in reducing the fungal density in cardiac vegetations (P < 0.03). However, as in the kidney, AmB plus Flu demonstrated antagonism versus AmB monotherapy in the treatment of C. albicans endocarditis (P < 0.05, P = 0.036, and P < 0.008 on days 5, 14, and 21, respectively).